Phytochemical and pharmacological evaluations of Polygonum lapathifolium stem extract for anthelmintic and antiemetic activity - Bulbul, Latifa; Sushanta, Somen Mojumder; Uddin, Md. Jahir; Tanni, Shahnaj (International Current Pharmaceutical Journal, 2013)
The present study is an attempt to preliminary phytochemical investigation, anthelmintic and anti-emetic activity studies on methanolic extract of Polygonum lapathifolium stems. The phytochemical screening shows the presence of phytosterols, diterpens, amino acid & protein, alkaloid and flavonoids, those are responsible for antiviral, antibacterial, antiallergic, antihypertensive, antiarrythmic, hepatoprotective, anti-inflammatory effects in mammals. In Anthelmintic activity test (using Pheretima posthuma model) five concentrations (20, 40, 60, 80 and 100 mg/ml in distilled water) of extracts were used which involved the determination of time of paralysis (vermifuge) and time of death (vermicidal activity) of the worms, where the concentration of 60, 80 &100 mg/ml showed a significant anthelmintic activity. Observations were comparable with the standard drug at concentration of 10mg/ml of piperizine citrate. On the other hand, in anti-emetic test, emesis was induced by the oral administration of copper sulphate 50mg/kg body weight to four days age of young chicks using chick emesis model. The antiemetic activity was determined by calculating the mean decrease in number of retching in contrast with those of control disorders. The extracts (150 mg /kg orally) showed statistically significant antiemetic effect (90.45% Inhibition) compared with reference drug metoclopramide (50mg/kg intraperitoneally) which showed 82.48% Inhibition. From these observations, it was concluded that stems extracts have potential anthelmintic and anti-emetic properties. The plant may further be explored for its various pharmacological activities. DOI: http://dx.doi.org/10.3329/icpj.v2i3.13582 International Current Pharmaceutical Journal, February 2013, 2(3): 57-62